Frequency of sexual dysfunction in outpatients with severe mental illness in Greece - Angelaki, Maria; Alexiou, Eirini; Igoumenou, Artemis; Alevizopoulos, Giorgos (Frontiers in Psychiatry, 2023)
Introduction Patients with psychosis can develop sexual dysfunction, which may be related to the disease itself, psychosocial factors, somatic comorbidities, and the use of psychotropic medication. Objective We aimed to investigate the type and frequency of sexual dysfunction in patients diagnosed with schizophrenia or bipolar disorder in order to assess the side effects of antipsychotics in sexual function. Methods This is a multicenter, cross-sectional study, involving patients diagnosed with schizophrenia (79.3%) or bipolar disorder (20.7%) treated in the Department of Psychiatry and Community Mental Health Centers from November 2018 to December 2019. Patients were enrolled in the study after signed informed consent. Demographic and clinical data were collected from patients through a semi-structured interview. The Antipsychotics and Sexual Functioning Questionnaire (ASFQ) was administered to assess sexual function. Results A total of 87 outpatients on antipsychotics were recruited in the study. The mean age was 43.6 years, while the mean duration of the disease was 16.9 years. Overall, only 9.1% of patients spontaneously reported sexual dysfunction. Patients treated with oral first-generation antipsychotics had more difficulties in achieving orgasm and decreased erection capacity. In contrast, patients treated with oral second-generation antipsychotics had decreased ejaculation capacity. Patients on antipsychotic combination therapy were associated with higher rates of sexual anhedonia. Discussion These results suggest that sexual dysfunction is a side effect of antipsychotic treatment, which was spontaneously rarely reported by patients. It seems essential to obtain a psychosexual clinical history before initiating antipsychotic treatment to evaluate following changes and adopt an individualized strategy to manage sexual dysfunction induced by antipsychotics.